2010
DOI: 10.1053/j.gastro.2010.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter Density Changes in Brains of Patients With Irritable Bowel Syndrome

Abstract: Background & Aims Several studies have examined structural brain changes associated with chronic pain syndromes, including irritable bowel syndrome (IBS), but study sample sizes have been small and heterogeneous. Methods We used magnetic resonance imaging (MRI)-based techniques, voxel-based morphometry, and cortical thickness analysis, to examine brain anatomical differences in a relatively large, tightly screened sample of IBS patients (n=55); we compared data with that from healthy individuals (controls, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
196
5
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(227 citation statements)
references
References 50 publications
19
196
5
3
Order By: Relevance
“…In agreement, early-life stress induces a decrease of hippocampal volume and functional alterations when measured in adulthood (Nemeroff, et al 2006). Structural changes have also been observed in IBS patients using brain imaging (Blankstein, et al 2010;Seminowicz, et al 2010). Also, circulating glucocorticoids can have contrasting effects in the amygdala and hippocampus, and these two structures can play contrasting roles in the activity of the HPA axis.…”
Section: The Synchronic Stress Engineeringmentioning
confidence: 50%
See 2 more Smart Citations
“…In agreement, early-life stress induces a decrease of hippocampal volume and functional alterations when measured in adulthood (Nemeroff, et al 2006). Structural changes have also been observed in IBS patients using brain imaging (Blankstein, et al 2010;Seminowicz, et al 2010). Also, circulating glucocorticoids can have contrasting effects in the amygdala and hippocampus, and these two structures can play contrasting roles in the activity of the HPA axis.…”
Section: The Synchronic Stress Engineeringmentioning
confidence: 50%
“…abnormal loci of cerebral activation) of pain was observed in IBS patients (Bonaz, et al 2002;Agostini, et al 2011). In addition, brain structural changes of the HPA axis and limbic structures have been recently reported in IBS patients (Blankstein, et al 2010;Seminowicz, et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…4 Several recently published studies have mapped IBS's relationship with psychological disorders [10][11][12][13][14][15][16] and compared depression and anxiety levels in IBS-subtypes. 15,17,18 However, the relationship between IBS and psychological disorders (depression or anxiety) was inconsistent, even in a recent meta-analysis entailing eight studies. 19 The heterogeneity of the results was too high, with no further analysis of its cause.…”
Section: Introductionmentioning
confidence: 99%